Implementation of Service Quality Improvement Strategies in Service Unit Division PT. Pos Indonesia (Persero) Jakarta - Rahman, Arif; Suhaila, Agus; Haryati, R.Ati (Journal of Industrial Engineering & Management Research, 2021)
Globalization demands an increasing change in all fields, one of which is the field of Services and services. Judging from the number of companies engaged in services and services, PT Pos Indonesia is required to have a special strategy to be able to compete with other companies. This study aims to find out how the strategies used to improve service quality, obstacles encountered, and how the solutions to overcome these obstacles. The research methodology used is a qualitative descriptive study using observational approaches, interviews, and documentation. With the results of research in the form of excellent service strategies by providing the best service to customers and service product development strategies that have been developed to facilitate customers running his business. Constraints in the form of lack of patience, technical and weather problems, accuracy, internet connection, when the COD of the recipient is not in place, and return of goods. And how to cope with extra patience, the existence of further communication and apologies, sorting goods so as not to be confused, fixing an internet connection, maintaining communication by contacting first that the recipient is in place, and ensuring the goods are damaged by the seller or courier